Dual-Mode Conical Horn Antenna with 2-D Azimuthal Monopulse Pattern for Millimeter-Wave Applications - Asrin Piroutiniya; Mohamad Hosein Rasekhmanesh; José Luis Masa-Campos; José Luis Calero-Rodríguez; Jorge A. Ruiz-Cruz (Sensors, 2023)
In this paper, a novel concept of a three-dimensional full metal system including a Dual-Mode Converter (DMC) network integrated with a high-gain Conical Horn Antenna (CHA) is presented. This system is designed for 5G millimeter wave applications requiring monopulse operation at K-band (<semantics>37.5–39<mtext> </mtext>GHz</semantics>). The DMC integrates two mode converters. They excite either the <semantics>TE11cir</semantics> or the <semantics>TE01cir</semantics> modes of the circular waveguide of the CHA. The input of the mode converters is the <semantics>TE10rec</semantics> mode of two independent WR-28 standard rectangular waveguide ports. By integrating the DMC with the CHA, the whole system, called a Dual-Mode Conical Horn Antenna (DM-CHA), is formed, radiating the sum (<semantics>Σ</semantics>) and difference (<semantics>Δ</semantics>) patterns associated to the monopulse operation. To adequately prevent the propagation of higher order modes and mode mutual coupling, this integration procedure is carefully designed and fabricated. To prove the performance of the design, the DMC network was fabricated using subtractive manufacturing by Computer Numerical Control (CNC) technology. The CHA was fabricated using additive manufacturing by Direct Metal Laser Sintering (DLMS) technology. Finally, the simulation and measurement results were exhaustively compared, including return loss, isolation, radiation pattern, and gain of the full DM-CHA structure. It is noteworthy that this system provided up to <semantics>±11°</semantics> per beam in the angular of arrival detection to support the high data rate operation for 5G satellite communications in the millimeter-wave band.